Determination of Plasmid pSN1216-29 Host Range and the Similarity in Oligonucleotide Composition Between Plasmid and Host Chromosomes - Tokuda, Maho; Suzuki, Haruo; Yanagiya, Kosuke; Yuki, Masahiro; Inoue, Kengo; Ohkuma, Moriya; Kimbara, Kazuhide; Shintani, Masaki (Frontiers in Microbiology, 2020)
Plasmids are extrachromosomal DNA that can be horizontally transferred between different bacterial cells by conjugation. Horizontal gene transfer of plasmids can promote rapid evolution and adaptation of bacteria by imparting various traits involved in antibiotic resistance, virulence, and metabolism to their hosts. The host range of plasmids is an important feature for understanding how they spread in environmental microbial communities. Earlier bioinformatics studies have demonstrated that plasmids are likely to have similar oligonucleotide (k-mer) compositions to their host chromosomes and that evolutionary host ranges of plasmids could be predicted from this similarity. However, there are no complementary studies to assess the consistency between the predicted evolutionary host range and experimentally determined replication/transfer host range of a plasmid. In the present study, the replication/transfer host range of a model plasmid, pSN1216-29, exogenously isolated from cow manure as a newly discovered self-transmissible plasmid, was experimentally determined within microbial communities extracted from soil and cow manure. In silico prediction of evolutionary host range was performed with the pSN1216-29 using its oligonucleotide compositions independently. The results showed that oligonucleotide compositions of the plasmid pSN1216-29 had more similarities to those of hosts (transconjugants genera) than those of non-hosts (other genera). These findings can contribute to the understanding of how plasmids behave in microbial communities, and aid in the designing of appropriate plasmid vectors for different bacteria.